Continuous Performance Test Is Sensitive to a Single Methylphenidate Challenge in Preschool Children With ADHD. Issue 2 (January 2020) - Peskin, Miriam; Sommerfeld, Eliane; Basford, Yael; Rozen, Shlomit; Zalsman, Gil; Weizman, Abraham; Manor, Iris
Objective: There is a lack of evidence-based diagnostic paradigms and personalized interventions for preschoolers with ADHD. This study aimed to evaluate the performance of preschoolers diagnosed with ADHD on a continuous performance test (CPT) before and after a single methylphenidate (MPH) challenge.Method: The Test of Variables of Attention (TOVA)—a CPT—was administered to 61 preschoolers (5.64 ± 0.69 years; 74% boys) with ADHD before and after a single MPH challenge (0.3 or 0.5 mg/kg). Baseline TOVA performance was correlated with Conners' Rating Scales (CRS) and compared with post-MPH TOVA performance.Results: A high rate of omission errors and several significant correlations between TOVA values and CRS scores were found at baseline. A single MPH administration improved TOVA performance significantly and was well tolerated.Conclusion: TOVA assessment may assist in the evaluation of the effect of MPH in preschoolers with ADHD and may help in planning interventions for them.